2002
DOI: 10.1176/appi.ajp.159.8.1367
|View full text |Cite
|
Sign up to set email alerts
|

Major Depression in Elderly Home Health Care Patients

Abstract: Geriatric major depression is twice as common in patients receiving home care as in those receiving primary care. Most depressions in patients receiving home care are untreated. The poor medical and functional status of these patients and the complex organizational structure of home health care pose a challenge for determining safe and effective strategies for treating depressed elderly home care patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
311
8
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 321 publications
(347 citation statements)
references
References 63 publications
21
311
8
4
Order By: Relevance
“…Many studies have reported that medical co-morbidity affects the feeling of well-being in late life and that chronic medical conditions increase the risk of depression (Cole and Dendukuri 2003;Djernes 2006;Bruce et al 2002). A study of older people in Greece also concurred with our finding (Papadopoulos et al 2005).…”
Section: Health Statussupporting
confidence: 90%
“…Many studies have reported that medical co-morbidity affects the feeling of well-being in late life and that chronic medical conditions increase the risk of depression (Cole and Dendukuri 2003;Djernes 2006;Bruce et al 2002). A study of older people in Greece also concurred with our finding (Papadopoulos et al 2005).…”
Section: Health Statussupporting
confidence: 90%
“…Home care has grown among the elderly in comparison with other types of care, and now represents 72% of health plan beneficiaries 12 .…”
Section: Discussionmentioning
confidence: 99%
“…The disorders that occur during the aging process can be ameliorated by actions that promote health and assist in the maintenance of the functional capacity of the elderly person. As such, home care programs represent one of the alternatives incentivized by the Brazilian government when facing such demand 12 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, MDD is evidenced in approximately 3-5% of community dwelling elders (Bruce, McAvay, & Raue, 2002). However, this percentage increases to roughly 20% of residents in skilled nursing facilities (Jones, Marcantonio, & Rabinowitz, 2003).…”
mentioning
confidence: 99%
“…However, this percentage increases to roughly 20% of residents in skilled nursing facilities (Jones, Marcantonio, & Rabinowitz, 2003). Rates of major depression in older adults who receive primary or home health care services or who reside in assisted living facilities fall within these bounds (e.g., Bruce et al, 2002;Watson, Garrett, Sloane, Gruber-Baldini, & Zimmerman, 2003).…”
mentioning
confidence: 99%